Topographic, vegetation, radiocarbon and stratigraphic data from Babitonga Bay-Santa Catarina-Brazil - Cohen, Marcelo Cancela Lisboa; Fontes, Neuza; Rodrigues, Érika do Socorro Ferreira; Pessenda, Luiz C R; França, Marlon; Garret, Ed; Ryu, Junghyung (PANGAEA, 2025)
Ground Control Points (topography) and vegetation data obtained along the coastal plain of Babitonga Bay- Santa Catarina, Brazil. Vegetation characteristics were measured in situ, and porewater salinity was measured with a refractometer. Radiocarbon, elemental, isotopic and pollen data were obtained along the cores SF-07 (26° 12' 50.5830 S, 48° 34' 27.9289 W, 15 cm above msl), SF-09 (26° 12' 54.5092 S, 48° 34' 27.7257 W, 190 cm above msl) and SF-10 (26° 12' 56.1458 S, 48° 34' 26.5479 W, 260 cm above msl). These cores were collected during the winter season in August 2017 using Russian-type sampling equipment. Sediment cores were obtained from tidal flats colonized by mangroves (SF-07), herbs (SF-09), and ombrophilous forest (SF-10).These data involves planialtimetric and stratigraphic analyzes, implemented in two phases: 1) Selection of mangrove areas for a topographic survey based on laser/GNSS data and aerophotogrammetry of drone images, and determination of the stature and species of mangrove trees (Vegetation and Ground Control Points Tables); 2) Selection of the core sampling sites for a paleoenvironmental reconstruction (Radiocarbon ages table). A Drone DJI Phantom 4 Advanced recorded ~1421 high spatial resolution photos (2.6 cm) by a digital 4K/20MP (RGB) camera to cover ~225 ha in Aug/2017 and Jun/2024 , following predetermined missions (90º camera angle, 90% frontal, and 75% lateral overlay, at 100 m altitude). Planialtimetric data (coordinates of Ground Control Points) were obtained by drone aerophotogrammetry using the Agisoft Metashape Professional version 1.8.4 (Ground Control Points Table). Radiocarbon dates (Radiocarbon Ages Table) were obtained by accelerator mass spectrometry (AMS) at the Center for Applied Isotope Studies (UGAMS) of the University of Georgia and International Chemical Analysis, Inc. Radiocarbon ages were normalized to a δ13C of −25‰ VPDB and reported as calibrated years (calibrated years before the present; 2σ) using CALIB 8.2 (Stuiver et al., 2017). The sediment cores were subsampled (1 cm³) at 5 cm intervals and processed using standard pollen analytical techniques, including acetolysis (Faegri and Iversen, 1989). Reference sources for pollen grain and spore identification included morphological descriptions by (Colinvaux P, 1999; Herrera and Urrego, 1996; Lorente et al., 2017). The table with pollen data shows the quantity of pollen taxa at each depth (Pollen Table). Sedimentary organic matter was treated with 4% HCl to eliminate carbonate, washed with distilled water (pH 6), and dried at 50°C. Total organic carbon was determined at the Stable Isotope Laboratory of the Center for Nuclear Energy in Agriculture/University of São Paulo (CENA/USP). Results are presented in percentages of dry weight, with a precision of 0.09% (Total Organic Carbon - TOC) (Isotopes 3 Table). The organic matter δ13C values are presented as δ13Corg (VPDB standard) with a precision of ±0.2‰ (Pessenda, 2004).
Keywords: isotopes; mangrove; radiocarbon age; South Brazil